Summary on Adverse Effects of Excess Iron - Thankachan, Prashanth; Kurpad, Anura (Indian Journal of Community Health, 2018)
India has made rapid economic progress, however most of this growth has been an inequitable progress leading to less than appreciable to minuscule changes on several health and nutritional status indicators, particularly anemia. prevalence of anemia among young women, pregnant women and children has seen little improvement in the last decade, with a rather small decline between 2005-06 to 2015-16(nfhs-3, nfhs-4). The etiology of anemia is multifactorial and often when high prevalence of anemia is seen, the most likely causal factor is nutritional deficiency of iron. Iron-deficiency anemia is a serious public-health concern not only in India but across most developing countries. It results in increased maternal mortality, morbidity and decreased child survival and is estimated to cause 591,000 perinatal deaths and 115,000 maternal deaths globally (1).